Spatially Resolved River Monitoring by UAV-Borne 4D-Imaging Radar: Experiments and Preliminary Validation - Giordano Cicioni; Federico Alimenti; Timo Grebner; Julian Kanz; Ron Riekenbrauck; Christian Waldschmidt (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
There is growing research interest in monitoring river discharge using noncontact sensors that do not require direct interaction with the water and can be mounter on unmanned aerial vehiclesto reach inaccessible areas. To this end, novel hydrodynamic models are being developed that allow the estimation of river discharge from river surface velocity measurements combined with bathymetry and water level. This research presents a novel data processing method for analyzing the surface velocity distribution of water flows using a 77-GHz 4-D imaging frequency modulated continuous wave (FMCW) radar sensor. Targets detected in the radar field-of-view are interpreted as surface velocity contributions, with the value of the surface velocity inferred from the radial component measured by the radar. We will first validate the sensor and algorithm in a controlled laboratory environment, and then deploy the system in various river environments, using both tripod-based and unmanned aerial vehicle (UAV)-based configurations. The final output, a georeferenced composite image derived from multiple UAV acquired radar images, provides detailed insights into complex, nonlaminar water flow patterns.